A Study of Problems and Needs in Forensic Evidence Collection among Emergency Nurses: Case Study of Khon Kaen 2 Hospital - แสงขาว กนกภรณ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to explore the problems and obstacles encountered by emergency department nurses in collecting forensic and medico-legal evidence in physical assault cases. Emergency nurses serve as frontline healthcare professionals who are often the first to have contact with victims. Their responsibilities include history taking, triage, documentation of injuries, providing medical care, and collecting and preserving forensic evidence. Biological specimens such as blood, urine, and feces, as well as physical evidence including clothing, glass fragments, stones, and weapon debris attached to wounds, may be obtained during clinical management. Inappropriate evidence handling may compromise the integrity and admissibility of forensic evidence in the judicial process. This qualitative study employed semi-structured interviews with 11 registered nurses working in the emergency department. Data were analyzed using content analysis. The findings revealed that the problems and obstacles could be categorized into four major domains: 1) knowledge and skills, 2) on-site management, 3) system limitations and workload, and 4) ethical and legal concerns. Furthermore, educational level, years of experience in the emergency department, and prior training in forensic and medico-legal practice were found to be associated with the types and extent of challenges encountered. A prominent issue identified was the lack of adequate training and continuing education in forensic and medico-legal evidence collection. The study recommends that hospitals systematically support continuing education and skill development in forensic practice to enhance nurses’ competencies, improve evidence quality, and strengthen the credibility of the justice process.